Understanding and measuring coordination and control in kicking skills in soccer: Implications for talent identification and skill acquisition - Davids, K.; Lees, A.; Burwitz, L. (Journal of Sports Sciences, 2000)
In this review, we explore the role of motor control and biomechanics in developing an understanding of soccer skills using kicking as the main vehicle. The links between these sub-disciplines of sport science have not been well established in the past because of an emphasis on cognitive processes in traditional accounts of motor behaviour. We argue that a dynamical systems interpretation of the processes of coordination and control in movements with multiple degrees of freedom signals a new era in the relationship between the sub-disciplines of motor control and biomechanics. Although research on coordination and control of soccer skills is currently sparse, there are indications that the relationship between motor control and biomechanics could form a significant component of scientific programmes in talent identification and skill development. Further interdisciplinary work is needed to enhance understanding of coordination and control of soccer skills.